Human Embryonic Stem Cell Responses to Ionizing Radiation Exposures: Current State of Knowledge and Future Challenges - Mykyta V. Sokolov; Ronald D. Neumann (Stem Cells International)
Human embryonic stem cells, which are derived from the inner cell mass of the blastocyst, have become an object of intense study over the last decade. They possess two unique properties that distinguish them from many other cell types: (i) the ability to self-renew indefinitely in culture under permissive conditions, and (ii) the pluripotency, defined as the capability of giving rise to all cell types of embryonic lineage under the guidance of the appropriate developmental cues. The focus of many recent efforts has been on the elucidating the signaling pathways and molecular networks operating in human embryonic stem cells. These cells hold great promise in cell-based regenerative therapies, disease modeling, drug screening and testing, assessing genotoxic and mutagenic risks associated with exposures to a variety of environmental factors, and so forth. Ionizing radiation is ubiquitous in nature, and it is widely used in diagnostic and therapeutic procedures in medicine. In this paper, our goal is to summarize the recent progress in understanding how human embryonic stem cells respond to ionizing radiation exposures, using novel methodologies based on “omics” approaches, and to provide a critical discussion of what remains unknown; thus proposing a roadmap for the future research in this area.